Kajian Atas Peraturan Menteri Perhubungan Republik Indonesia Nomor 118 Tahun 2018 Tentang Penyelenggaraan Angkutan Sewa Khusus Terhadap Driver Taksi Online Di Kota Surakarta - Andrian Bagus Setyawan; Rosita Candarakirana (Faculty of Law Universitas Sebelas Maret Surakarta, 2020)
This study aims to see to what extent the Regulation of the Minister of Transportation of the Republic of Indonesia Number 118 of 2018 concerning the Implementation of Special Rental Transportation is the perfect reference for online taxi drivers in the city of Surakarta. This study uses a descriptive normative method with a quantitative approach. The data source comes from primary data sources, namely the 1945 Constitution of the Republic of Indonesia and other laws. The secondary data source comes from direct interviews with online taxi drivers in the city of Surakarta.The implementation of partner collaboration between online taxi drivers and the applicator as a partner provider company has resulted in several obstacles that are detrimental to online taxi drivers in terms of the coverage of customer collection areas, minimum rates that are not in accordance with the rules, and the absence of the influence of monitoring tools provided by the applicator to security of online taxi drivers and customers. Given that there are still many shortcomings felt by online taxi drivers, this needs to be a major concern.